The characteristics of vHIT gain and PR score in peripheral vestibular disorders. (2nd January 2021) - Du, Yi; Ren, Lili; Liu, Xingjian; Guo, Weiwei; Wu, Ziming; Yang, Shiming
Abstract: Background: Clinical application of vHIT is limited due to a lack of interpretation of vHIT gain and saccades. Objectives: This research focuses on comparing common vertigo diseases on vHIT gain and saccade divergence(PR score). Material and Methods: We retrospectively reviewed 165 patients who have one definite diagnosis, good data quality, and can be read by MATLAB software. All patients were grouped into unilateral vestibular dysfunction (UVD), Meniere's disease (MD), vestibular migraine (VM), Ramsay Hunt Syndrome (RHS), bilateral vestibular hypofunction (BVH), benign paroxysmal positional vertigo (BPPV), and acoustic neuroma (AN). PR score was calculated by an open-source software HitCal. Results: The saccade detection rate is higher than the abnormal vHIT gain on UVD, MD, VM, RHS, BVH and BPPV. PR score combined with vHIT gain could separate the affected side in UVD and RHS. In the MD group, both vHIT gain and PR score have inconspicuous performance. We also found that different compensation levels and hearing loss status affect results. Conclusions and Significance: vHIT gain combined with PR score enables a proper distinction among common vertigo diseases. PR score is more sensitive than the gain value on evaluating the physiological situation, vestibular compensation and disease progression.